2019
DOI: 10.3390/biology8030054
|View full text |Cite
|
Sign up to set email alerts
|

Chronotype and Social Jetlag: A (Self-) Critical Review

Abstract: The Munich ChronoType Questionnaire (MCTQ) has now been available for more than 15 years and its original publication has been cited 1240 times (Google Scholar, May 2019). Additionally, its online version, which was available until July 2017, produced almost 300,000 entries from all over the world (MCTQ database). The MCTQ has gone through several versions, has been translated into 13 languages, and has been validated against other more objective measures of daily timing in several independent studies. Besides… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
426
4
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 449 publications
(447 citation statements)
references
References 106 publications
11
426
4
6
Order By: Relevance
“…In this study, we found similar results, that night time texting use of cell phones is significantly associated with social jetlag (Gradisar et al, 2013). Studies have identified a statistically significant association between social jetlag and health-related disorders, and they also showed that irregular sleep timing is associated with an unhealthy lifestyle (Roenneberg et al, 2019). Additionally, social jetlag and its association with adverse health outcomes are often studied as a sleep discrepancy, and there is currently no consensus on outcomes (Roenneberg et al, 2019).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In this study, we found similar results, that night time texting use of cell phones is significantly associated with social jetlag (Gradisar et al, 2013). Studies have identified a statistically significant association between social jetlag and health-related disorders, and they also showed that irregular sleep timing is associated with an unhealthy lifestyle (Roenneberg et al, 2019). Additionally, social jetlag and its association with adverse health outcomes are often studied as a sleep discrepancy, and there is currently no consensus on outcomes (Roenneberg et al, 2019).…”
Section: Discussionsupporting
confidence: 81%
“…Studies have identified a statistically significant association between social jetlag and health-related disorders, and they also showed that irregular sleep timing is associated with an unhealthy lifestyle (Roenneberg et al, 2019). Additionally, social jetlag and its association with adverse health outcomes are often studied as a sleep discrepancy, and there is currently no consensus on outcomes (Roenneberg et al, 2019). Therefore, in social jetlag studies, final outcomes are often described in terms of sleep habits.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, adolescents and college-aged individuals push activities to a later clock time, and thus, present a greater risk of a mild kind of circadian misalignment, denominated social jet lag [3]. The latter is a condition characterized by discrepancy in sleep/wake schedules on weekends versus weekdays [4]. Importantly, social jet lag is considered a potential risk factor for obesity and unhealthy dietary habits among young adults, as was recently shown by our research group [5].…”
Section: Introductionmentioning
confidence: 62%
“…Chronotype may refer to actual and/or preferred timing of sleep/wake behaviours [4], and individuals with evening preference/later chronotype may experience impaired sleep quality [5,6]. Similarly, social jetlag (SJL), the manifestation of differences in sleep timings on "free" and "work" days arising as a conflict between social schedules and the internal circadian clock [7], may also be associated with impaired sleep quality [8]. Furthermore, chronotype is influenced by sex and changes through the lifespan (being male, and an adolescent or young adult, are associated with later chronotype) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, chronotype is influenced by sex and changes through the lifespan (being male, and an adolescent or young adult, are associated with later chronotype) [9]. Greater SJL is most common with later chronotype [7], and therefore, by extension, may be influenced by age and sex as being males and in the age range of the late teens to early twenties is associated with both greatest SJL and later, chronotype [7]. Subjective sleep quality also decreases with increasing age [10].…”
Section: Introductionmentioning
confidence: 99%